Multilevel Analysis of School Performance in Mathematics for Fourth Grade of Basic Education in Colombia - Zambrano Jurado, Juan Carlos (Sociedad y Economía, 2013)
The study analyses the role of factors such as family, school, socio-economic conditionsof students, teaching methods and practices, to determine how they affect the scopeof educational achievements in the field of mathematics, using data from TIMSS 2007.The results show an increased performance for boys compared with that achieved bygirls. The variables with the greatest impact are: the type of school, liking for mathematics,zone and school liking, explained by personal characteristics and the institution towhich the students belong.